Aharonov-Bohm effect: analysis of scattering in the forward direction - Vlasii, N.D. (Вопросы атомной науки и техники, 2012)
The long-standing problem of a divergent behaviour of the Aharonov-Bohm scattering amplitude in the forward direction is reconsidered. We show that this divergence has no physical consequences, being an artefact of the approximation that neglects the transverse size of a magnetic vortex. As long as the vortex transverse size is taken into account, this divergence is tamed but, however, in a certain sense manifests itself as a forward peak of the Fraunhofer diffraction. The peak is becoming more transparent in the limit of high energies of scattered particles. Рассматривается давно существующая проблема расходимости амплитуды рассеяния Ааронова-Бома в направлении вперед. Мы показываем, что эта расходимость не имеет физических последствий, являясь искусственным следствием приближения, которое не учитывает поперечных размеров магнитного вихря. Как только поперечные размеры вихря принимаются во внимание, эта расходимость исчезает, но, однако, в некотором смысле проявляется как пик фраунгоферовской дифракции в направлении вперед. Пик становится более выраженным в пределе высоких энергий рассеиваемых частиц. Розглядається давно існуюча проблема розбіжності амплітуди розсіяння Ааронова-Бома в напрямку вперед. Ми показуємо, що ця розбіжність не має фізичних наслідків, оскільки сама є штучним наслідком наближення, котре нехтує поперечними розмірами магнітного вихора. Як тільки поперечні розміри вихора враховуються, ця розбіжність зникає, проте, все ж таки, певним чином проявляється як пік фраунгоферової дифракції в напрямку вперед. Пік стає більш виразним в границі високих енергій розсіюваних частинок.